Sosialisasi Pemasangan Titik Gogle Maps Dan Spanduk Sebagai Alat Promosi Dalam perluasan Jaringan Penjualan Umkm RT 09 RW 05 Kelurahan Pematang Gubernur Kota Bengkulu - Dona, Hesti Pestiko; Patriasia, Eka Salsa; Anggreani , Wike; Abdullah , Hasan; Saputra , Sandi; Putra, Dwingki Marta; Abi, Yudi Irawan; Gayatri, Ida Ayu Made Er Meytha (Jurnal Kewirausahaan dan Bisnis, 2025)
Rt 09 Rw 05 in the Pematang Gubernur village holds great potential in the field of Micro, Small, and Medium Enterprises (MSMEs). However, this potential has not yet been fully explored and recognized by the wider community. Seeing this opportunity, students conducting Community Service (KKN) in Rt 09 Rw 05 initiated an innovative program, which includes the installation of map points and the posting of banners design for MSMEs. This program aims to highlight the village's potential and to introduce superior products to a broader audience. In the era of digitalization, MSMEs still do not understand how to place their Google Maps location as one of the economic drivers of developing countries. Micro and small enterprises (MSMEs) have a significant role. With the existence of MSMEs, in this activity, KKN students provide training and direct assistance to MSME owners to operate the step-by-step registration of their business on Google Maps so that its visibility can be seen by the public. Through the implementation of this work program, it is expected that MSME owners can better understand and appreciate the importance of digitalization in managing their businesses. By utilizing digital technology, MSME players will make it easier for potential customers to find their business locations more effectively and efficiently. This is expected to positively impact the increase in sales volume and expand their market reach. In addition, this program aims to improving the efficiency and productivity of MSMEs, allowing them to optimize existing resources and minimize waste. With digitization, MSMEs can also create significant added value at the village level, contributing to local economic growth and strengthening their position in an increasingly competitive market. Through this approach, it is hoped that MSMEs can not only survive but also grow and compete effectively in the digital era.